Transcriptome Analysis of Ovarian Follicles Reveals Potential Pivotal Genes Associated With Increased and Decreased Rates of Chicken Egg Production - Chen, Xiaoxia; Sun, Xue; Chimbaka, Ignatius Musenge; Qin, Ning; Xu, Xiaoxing; Liswaniso, Simushi; Xu, Rifu; Gonzalez, John Michael (Frontiers in Genetics, 2021)
Egg production is an important economic trait in the commercial poultry industry. Ovarian follicle development plays a pivotal role in regulation of laying hen performance and reproductive physiology. However, the key genes and signaling pathways involved in the various-stages of laying hen follicular development remain poorly understood. In this study, transcriptomes of ovarian follicles at three developmental stages, the large white follicle (LWF), small yellow follicle (SYF), and large yellow follicle (LYF), were comparatively analyzed in hens with high (HR) and low (LR) egg-laying rates by RNA-sequencing. Eighteen cDNA libraries were constructed and a total of 236, 544 and 386 unigenes were significantly differentially expressed in the LWF, SYF, and LYF follicles of HR and LR hens, respectively. Among them, 47 co-transcribed differentially expressed genes (DEGs) in LWF and SYF, 68 co-expressed DEGs in SYF and LYF, and 54 co-expressed DEGs in LWF and LYF were mined. Thirteen co-expressed DEGs were found in LWF, SYF, and LYF follicles. Eighteen candidate genes, including P2RX1, CAB39L, BLK, CSMD3, GPR65, ADRB2, CSMD1, PLPP4, ATF3, PRLL, STMN3, RORB, PIK3R1, PERP1, ACSBG1, MRTO4, CDKN1A and EDA2R were identified to be potentially related to egg production. Furthermore, Kyoto Encyclopedia of Genes and Genomes analysis indicated neuroactive ligand-receptor interaction, cell adhesion molecules, peroxisome proliferator-activated receptor pathway, and cAMP signaling pathway might elicit an important role in formation of egg-laying traits by influencing ovarian follicle development. This study represents the first transcriptome analysis of various-sized follicles between HR and LR hens. These results provide useful molecular evidence for elucidating the genetic mechanism underlying ovarian follicle development associated with egg production in chicken.